Sexual harassment in sports: Risk factors analysis from a Malaysian perspective - Syahirah S.; Syarifah Fathynah S.S.; Melati W.P.; Puteh F.; Hamid B.A.; Ismail H. (Hampstead Psychological Associates, 2024)
Indexed by Scopus/ERA